Bram Stoker's Dracula : sucking through the century, 1897-1997 - Simpson-Housley, Paul; Davison, Carol Margaret (Dundurn Press, 1997)
A collection of essays by some of the world's leading scholars analyzing and celebrating the novel's legacy in popular culture.
Keywords: Stoker, Bram, : 1847-1912 : Dracula; Dracula, : Count (Fictitious character); Stoker, Bram : Dracula; Dracula (Stoker, Bram); Vampires; Dracula (Personnage fictif); LITERARY CRITICISM : European : English, Irish, Scottish, Welsh; Rezeption; Vampyrer i litteraturen; Vampyrfilm; Dracula, Count (Fictitious character)